Welfare in the nash equilibrium in export taxes und Bertrand duopoly - Roger Clarke; David R. Collie (Cardiff University, Cardiff Business School, 2006)
In the Eaton and Grossman (1986) model of export taxes under Bertrand duopoly, it is shown that welfare in the Nash equilibrium in export taxes is always higher than welfare under free trade for both countries.
Keywords: F12; F13; L13; 330; Trade Policy; Imperfect Competition; Oligopoly